The vertical drop jump is a poor screening test for ACL injuries in female elite soccer and handball players: A prospective cohort study of 710 athletes - Krosshaug, T.; Steffen, K.; Kristianslund, E.; Nilstad, A.; Mok, K.-M.; Myklebust, G.; Andersen, T. E.; Holme, I.; Engebretsen, L.; Bahr, R. (The American Journal of Sports Medicine, 2016)
Background: The evidence linking knee kinematics and kinetics during a vertical drop jump (VDJ) to anterior cruciate ligament (ACL) injury risk is restricted to a single small sample. Still, the VDJ test continues to be advocated for clinical screening purposes.